The Problems of Using Figurative Language (Comparison Contrast, Associaton, and Emphasis) in the 2024 Presidential Election by Netizens Media: A Stylistic Study - Dita Mulyana Ramadhani; Budi Prayetno; Muh.Inayah A.M; Sigit Tri Nova; Muh. Imam Hidayat RM; Sulistiawati Sulistiawati (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the issues surrounding the use of figurative language, specifically comparison, contrast, association, and emphasis, in the discussions of netizens on social media related to the 2024 Presidential Election. Using a stylistic approach, this research seeks to analyze how netizens use figurative language to express political views, criticism, and support for presidential candidates. Data were collected from posts and comments related to the presidential election topic on various social media platforms, such as Facebook, TikTok, and Instagram. A qualitative descriptive analysis method was employed to identify and categorize the use of these language styles. The results show that comparison and emphasis are frequently used by netizens to reinforce opinions and build a positive image of the supported presidential candidates. On the other hand, contrast is more often found in comments containing criticism and political debates. In conclusion, figurative language plays a significant role in the dynamics of social interaction and political communication among netizens on social media, reflecting high public engagement in national political issues. This research contributes to the study of political language and social interaction in the digital era.